A mitochondrial and lysosomal targeted ratiometric probe for detecting intracellular H2S. Issue 2 (22nd December 2021) - Liu, Wenjie; Bu, Dandan; Zhang, Hongyan; Zhang, Meng; Ren, Haohui; Li, Zhanxian; Yu, Mingming
Abstract : A dual-wavelength excitation ratiometric fluorescent probe, HABA, was prepared to detect H2 S. HABA had excellent localization abilities toward mitochondria and lysosomes. HABA can not only detect exogenous H2 S, but it can also detect endogenous H2 S. Abstract : Based on coumarin and benzopyran derivatives, a dual-wavelength excitation ratiometric fluorescent probe, HABA, was prepared to detect H2 S. The HABA probe showed good selectivity and anti-interference abilities during H2 S detection. Fluorescence co-localization experiments showed that HABA had excellent localization abilities toward mitochondria and lysosomes. More importantly, HABA can not only detect exogenous H2 S, but it can also detect endogenous H2 S, indicating that HABA has high application potential and value in the biological field.